Miłość i poezja w Elegii 2.30 Sekstusa Propercjusza - Bobrowski, Antoni (Collectanea Philologica, 2021)
Elegy 2.30 has been considered to be one of Propertius’ most difficult poems due to its complicated sequence of thought and distant associations noticeable in the discourse, which was often the reason for dividing the text into two separate poems. The article is an interpretative proposal aimed at demonstrating the integrity of 2.30, which was obtained by the poet by combining the concept of love with the concept of love poetry, as well as by using subtly constructed mythological references.